Preexisting High Expression of Matrix Metalloproteinase-2 in Tunica Media of Saphenous Vein Conduits Is Associated with Unfavorable Long-Term Outcomes after Coronary Artery Bypass Grafting - Nowicki, Michał; Zabel, Maciej; Ostalska-Nowicka, Danuta; Misterski, Marcin; Malinska, Agnieszka; Perek, Bartlomiej; Perek, Anna (BioMed research international, 2013)
Migration of the smooth muscle cells (SMCs) to the tunica media in the saphenous vein (SV) transplants is facilitated by matrix metalloproteinases (MMPs). The aim of this study was to identify any associations between expression of MMP-2 or endogenous tissue inhibitors (TIMP-2 and TIMP-3) in the SV segments and late failure of the SV grafts. Methods. Two hundred consecutive patients with a mean age of 63.1 ± 8.9 years who underwent primary isolated venous CABG were examined. Patients were retrospectively split into two subgroups, with the SV graft disease (SVGD (+); n=47) or without it (SVGD (−); n=153). In the SV segments, immunohistochemical analysis of the expression of the MMP-2, TIMP-2, and -3 was performed. Results. In the SVGD (+) patients, tissue expression of MMP-2 was stronger, whereas that of both TIMPs was weaker than in the SVGD (−) patients. In majority of the SV segments obtained from the SVGD (−) individuals, a balance in MMP and TIMP expressions was found, whereas an upregulation of MMP-2 expression was usually noted in the SVGD (+) subjects. Conclusion. The strong expression of MMP-2 accompanied by reduced immunostaining of both TIMPs is associated with the development of the SV graft disease and unfavorable CABG outcomes.